Exploring eye health professionals’ knowledge, attitudes and practices towards eye health promotion interventions: a cross-sectional study - Hlabje Carel Masemola; Olivia Baloyi; Zamadonda Nokuthula Xulu-Kasaba (Frontiers in Public Health)
BackgroundHealth promotion interventions are essential for preventing eye diseases and ensuring early diagnosis, particularly in underserved regions. In South Africa, the public sector has prioritized outreach activities; however, the availability and implementation of such strategies remain unclear. The study seeks to assess the knowledge, attitudes, and practices of eye health professionals regarding the implementation of health promotion interventions particularly those delivered through outreach activities.MethodA cross-sectional quantitative study was conducted in five districts of a South African province among 68 public sector optometrists. Data were collected using a structured self-administered questionnaire. Descriptive statistics, chi-square tests, logistic regression, and Spearman’s correlation were used to analyse the data.ResultsMost participants reported engaging in schools (89.7%) and community outreaches (95.6%), although collaboration with other professionals was limited. A high proportion of respondents demonstrated good knowledge (88.2%) and positive attitudes (89.7%) towards health promotion. Knowledge and attitude were significantly correlated (r = 0.477, p < 0.01). However, there was a noticeable gap between positive perceptions and consistent implementation of health promotion practices, especially those requiring inter-professional coordination.ConclusionEye health professionals in Limpopo Province have good knowledge and favourable attitudes towards health promotion, but implementation remains inconsistent due to systemic barriers. Strengthening HP training, formalizing outreach responsibilities, and improving inter-professional collaboration could enhance the effectiveness of health promotion strategies.